Evaluation of Ambidexterity in Pesantren Curriculum Management: Evaluasi Ambidexterity dalam Manajemen Kurikulum Pesantren - Sanafiri, Ahmad Nadif; Abdullah, Abdullah (Idarotuna : Journal of Administrative Science, 2024)
This research aims to evaluate the effectiveness of ambidextrous-based curriculum management strategies in the Jalaluddin Ar-Rumi Area of Nurul Jadid Islamic Boarding School, which integrates traditional teaching methods with innovative elements to enhance the quality of education. Using a qualitative approach, this study involves teachers, students, and curriculum managers as subjects, with data collected through in-depth interviews, surveys, and classroom observations. Data analysis techniques include thematic analysis to identify patterns from interviews and observations, as well as statistical analysis for survey data. The research results indicate that the strategy successfully improved teaching effectiveness and the learning experience for most teachers and students, although there were challenges in the consistency of implementation. Some teachers experienced difficulties in adopting the new methods, which resulted in uneven implementation outcomes. These findings highlight the need for regular evaluations and additional training to address shortcomings and ensure that the curriculum strategy optimally benefits all parties involved.